Comprehensive Synthesis Study of Well-Dispersed and Solution-Processed Metal Nanowires for Transparent Heaters. (9th May 2018) - Bobinger, Marco; Dergianlis, Vasileios; Becherer, Markus; Lugli, Paolo
Abstract : We review and extend the numerous polyol-based synthesis protocols and postdeposition treatments that have been reported for silver nanowires (AgNWs). After tailoring substantial process parameters such as the process time, temperature as well as the stirring speed, the polyvinylpyrrolidone (PVP) to silver nitrate (AgNO3 ) ratio, and the type of PVP, a high mean aspect ratio of 800 could be achieved. Interestingly, the addition of a small portion of potassium chloride (KCl) not only leads to a reduction in diameter but also extremely enhances the nanowire dispersion and its stability. This effect is attributed to the role of KCl, which, along with PVP, acts as a cocapping agent. Furthermore, sprayed AgNW and copper nanowire (CuNW) films were tested as transparent heaters. The AgNWs could be operated at a power density of at least 0.72 W/cm 2, which corresponds to a temperature of 213°C, whereas the CuNWs failed at a power density and temperature of 0.4 W/cm 2 and 150°C, respectively. Interestingly, the degradation of AgNWs shows a step-wise behavior and is mainly dominated by fragmentation, while the CuNWs are gradually oxidized.